Stosowanie środków specjalnych – nadzoru ochronnego i ośrodka przystosowania społecznego – wobec recydywistów skazanych w warunkach art. 60 k.k. - Rzeplińska Irena (Archiwum Kryminologii, 1982)
1. The Penal Code of 1969 introduced in Chapter VIII a complex of regulations defining the criminal liability tfor offences committed in the conditions of special recidivism. Two categories of special recidivism were introduced: basic recidivism (Art. 60 § 1 of the Penal Code) and multiple recidivism (Art. 60 § 2 of the Penal Code). To assume the first category, the following criteria are required: 1) commission of an intentional offence similar to the previous one, 2) execution of at least 6 months of imprisonment, 3) commission of a new offence within 5 years after discharge from prison. To impute the offender the commission of an offence coming under the second category of recidivism, the following conditions are necessary: 1) conviction for at least the fourth time, in this twice under the conditions of basic special recidivism, 2) repeated commision of an intentional offence to profit financially or of hooligan character, 3) total imprisonment of at least one year, 4) commission of a new offence within 5 years after the last imprisonment. For each of those two categories of recidivism, the principles of aggravated criminal liability are fixed by the Code, and they refer to less - serious - offences only. Towards persons coming under Art. 60 § 1 and 2, imprisonment within the raised limits is adjudicated. Towards such persons, absolute suppression of suspension of the execution of penalty was formulated. The strictness of these regulations is partly diminished by Art. 61 of the Penal Code, which created the possibility to depart from the aggravation of penalty as expressed in Art. 60, in "particularly justified cases, when even the lowest penalty inflicted on the basis of Art. 60 § 1 and 2 of the Penal Code, would be incommensurably severe". The Code fights special recidivism also by providing special measures against special recidivists coming under Art. 69 § 1 and 2: protective supervision (called "supervision" further on) and social readaptation centre (called "centre" further on). The first of them - supervision - is a non isolating measure, consisting in the control of behavior of the supervised person in the conditions of liberty. It is adjudicated for a period of 3 to 5 years (Art. 63 § 1 of the Penal Code). The second measure - centre - is of isolating character. The duration of stay in the centre is not appointed beforehand in the sentence: it is at least 2 years, at most 5 years long. After 2 years, the recidivist may be discharged by the execution of penalty court if there are good reasons to presume that he will not commit any offence after discharge (Art. 65 of the Penal Code). Special measures are executed after the sentence has been served. The principles of application of the special measures differ as regards both categories of recidivists: those coming under Art. 60 § 1 of the Penal Code (called "common recidivists" further on) and those coming under Art. 60 § 2 (called further "multiple recidivists"). The organs authorized to adjudge these measures are the criminal and execution of penalty courts. Their decision as to adjudgement of them may be taken at various stages of legal and executive proceedings: in the sentence (criminal court), in the latter part of imprisonment (execution of penalty court), and during the supervision (execution of penalty court).